2023
DOI: 10.1007/s11628-023-00549-5
|View full text |Cite
|
Sign up to set email alerts
|

Flash sales: how consumers’ emotional responses to negative word-of-mouth affect diagnosticity and purchase intentions

Wee-Kheng Tan,
Po-Yen Chen

Abstract: Using information–cognition–intention model and by comparing emotional and rational negative word-of-mouth (nWOM), this study considered nWOM’s role in online flash sales by examining whether consumers would find nWOM diagnostic and lower purchase intentions during flash sales. Partial least squares analysis of 308 questionnaires (150 for emotional and 158 for rational nWOM) revealed that worry, skepticism, and optimism emotions resulting from reading nWOM played a more limited than those of gratitude. Perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“… Numerous studies have demonstrated the relationship between emotions and cognition (e.g., attitude, intention, etc.) [19,20,22,32,33]. These studies emphasized the effect of emotional components (such as emotional states, fear, sadness, etc.)…”
Section: -1-literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“… Numerous studies have demonstrated the relationship between emotions and cognition (e.g., attitude, intention, etc.) [19,20,22,32,33]. These studies emphasized the effect of emotional components (such as emotional states, fear, sadness, etc.)…”
Section: -1-literature Reviewmentioning
confidence: 99%
“…Nevertheless, this approach has four fundamental gaps, including context (primarily limited to marketing and consumer behavior areas), study design (a lack of causality and common method biases), mediation and moderation effects in SEM, and external influences [3]. Besides, most previous studies concentrated on factors (subjective norms and perceived behavioral control) impacting attitudes and intentions in the decision-making process [19][20][21][22]; however, the emotional and rational aspects of attitudes and intentions were not strong enough to make the final decision and corresponded to remembering or knowing levels [23,24]. Based on these arguments, the last aim of this research is to build up a research model that combines both emotional and rational factors in explaining decision-making and considers the mediating role of rational factors in the relationship between emotions and decision-making.…”
Section: -Introductionmentioning
confidence: 99%
“…Line, Hanks, and Dogru [19] and Chen, Law, and Yan [20] highlight that electronic word-of-mouth (eWOM) monitoring is very important for restaurants because many restaurant consumers read and share information about their experiences on social media [21]. Word of mouth (WOM) reflects the affective aspects of a customer's experience with opinions comprising personal feelings and judgements [22]. Positive word-of-mouth (WOM) communication from tourists satisfied with their experiences has become a major source of competitive advantage [17].…”
Section: Introductionmentioning
confidence: 99%